TELAAH KESIAPAN DAN PROSPEK IMPLEMENTASI SAK ETAP: STUDI KASUS PADA PENGUSAHA UMKM GARMEN DI PUSAT GROSIR SURABAYA - SETIADY, MARRY (: 2303-1719)
Standar Akuntansi untuk Entitas tanpa Akuntabilitas Publik (SAK ETAP) was made and approved by DSAK-IAI as an alternative form of a simplified accounting standards that can be used by entities without public accountability for the implementation of accounting system better. The term entity without public accountability refers to Micro, Small and Medium Enterprises or so called SMEs. DSAK-IAI hopes that this SAK ETAP can make SMEs in Indonesia have a better accounting system to create financial statements that can be used independently for the importance of corporate decision making as well as interests of obtaining loans for business development. Research to examine the extent to which actors readiness of SMEs in implementing SAK ETAP with the sample garment SMEs in Pusat Grosir Surabaya was conducted by distributing questionnaires in advance. A total of 140 questionnaires have been distributed and only 97 questionnaires that can be processed into a data. The result showed that 44,33% of perpetrators of garment SMEs in the Pusat Grosir Surabaya was ready to implement SAK ETAP so in this study also provided advice on the draft of financial statements in accordance with SAK ETAP and business characteristics of garment SMEs in Pusat Grosir Surabaya.